Flowers of Shanghai [videorecording (DVD)] - Hou, Xiaoxian, 1947-; Leung, Tony Chiu Wai, 1962-; Hada, Michiko, 1968-; Reis, Michelle Monique, 1970-; Han, Bangqing, 1856-1894 (Criterion collection, 2021)
Follows the lives of five beautiful courtesans working in different brothels in nineteenth-century Shanghai.